2007
DOI: 10.1007/s10935-007-0114-8
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Multicultural Prevention Intervention among Urban American Indian Youth in the Southwest U.S.

Abstract: This study explored how a non-targeted group of ethnic minority youth might or might not benefit from a prevention intervention focused on other cultural groups. The study specifically evaluated the effects of an evidence-based drug prevention curriculum with a sample of urban American Indian youth in the southwest U.S., most of whom self-reported multi-ethnic heritages. Using growth curve modeling, this research examined the developmental trajectory of drug use for these youth, and compared it with the trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 49 publications
0
63
0
Order By: Relevance
“…Urban American Indian (AI) youth were not benefiting from KiR as much as other children (Dixon et al, 2007). Following the principles of community-based participatory research, a steering group, including leaders from the local urban AI community and school district personnel in charge of AI programs, was formed to guide the adaptation process.…”
Section: Case Study: Adaptations Of Keepin’it Real (Kir) the Southwementioning
confidence: 99%
“…Urban American Indian (AI) youth were not benefiting from KiR as much as other children (Dixon et al, 2007). Following the principles of community-based participatory research, a steering group, including leaders from the local urban AI community and school district personnel in charge of AI programs, was formed to guide the adaptation process.…”
Section: Case Study: Adaptations Of Keepin’it Real (Kir) the Southwementioning
confidence: 99%
“…With respect to consistency of findings, school-based preventive interventions addressing both substance abuse (Schinke et al, 1988; Schinke, Tapevac, & Cole, 2000) and suicide (LaFromboise & Howard-Pitney, 1994; 1995; LaFromboise & Lewis, 2008) vary considerably in yielding positive (Schinke, Tapevac, & Cole, 2000; LaFromboise & Howard-Pitney, 1994; 1995; Johnson et al 2009) versus negative (Dixon et al, 2007) individual level short-term outcomes. In one case, the Zuni Life Skills curriculum, which initially yielded favorable outcomes (LaFromboise & Pitney, 1994, 1995), was adapted for use across a diversity of AI/AN communities.…”
Section: Alcohol Abuse and Suicide Risk Preventive Interventions For mentioning
confidence: 99%
“…Some interventions were developed primarily by community members in response to community issues (Coyhis & Simonelli, 2008; Dorpat, 1994; Petoskey et al, 1998; Tower, 1989). However, most fit more traditional models of community-researcher collaboration, such as consulting with AI youth and elders to tailor/adapt an intervention for AI youth (Marlatt et al 2003) or attempting to replicate an intervention found efficacious among non-AI youth (Dixon et al, 2007). Finally, two intervention reports do not describe the collaboration process at all (Schinke et al, 1988; Schinke et al, 2000).…”
Section: Alcohol Abuse and Suicide Risk Preventive Interventions For mentioning
confidence: 99%
“…For example, compared to other racial/ethnic groups, AI/ANs between the ages of 15 and 24 have the highest suicide rates in the United States (CDC 2004). In addition, AI/AN youths have an earlier onset, experience significantly higher rates of alcohol and illicit drug use, and experience more severe consequences of drug use compared to any other ethnic/racial group in the United States (Dixon et al 2007). Also, among AI adolescents and young adults, ages 15-24, deaths attributable to alcoholism were found to be more than 15 times those of the same age group of all races combined (Mitchell, Beals & Whitesell 2008).…”
mentioning
confidence: 99%